Improve the Photocatalytic Hydrogen Production Using ZnS@ZnO Twin‐Junction Structure with Isoelectronic Traps. Issue 20 (14th June 2022) - Li, Zehan; Huang, Meiling; Li, Yanlu; Ai, Zizheng; Zhang, Kang; Yao, Xiaogang; Kong, Zhen; Shao, Yongliang; Wu, Yongzhong; Hao, Xiaopeng
Abstract: The effective separation of carriers with prolonged lifetime is important to improve the activity of photocatalytic water splitting hydrogen production. In this work, the separation of electron‐hole pairs is achieved by ZnS@ZnO twin‐junction with isoelectronic traps, with which the corresponding doubled fluorescence lifetime is achieved. The existence of isoelectronic traps is further confirmed by the first principles calculations that prove the coincidence between impurity level position and Fermi level. The all‐important role of isoelectronic traps has almost never been mentioned and demonstrated in photocatalysis so far. Moreover, it is favorable for photocatalysis that the migration direction of carriers in II‐type ZnS@ZnO is consistent with the trapped behavior under the effect of isoelectronic traps, which shows a leading H2 production activity of 1628 µmol h ‐1 g ‐1 under simulated sunlight. What's more, the impurity levels formed by sulfur in the middle part ZnO1‐ x S x enable visible light to be absorbed, neither ZnS nor ZnO would otherwise absorb visible light, and the H2 production activity reaches 380 µmol h ‐1 g ‐1 . This will provide guidance to construct composite structure for wide bandgap semiconductors in the future. Abstract : The II‐type ZnS@ZnO twin‐junction structure is constructed by ZnO and ZnS, with which the electron‐hole separation is achieved. The sulfuration produces isoelectronic traps so that the ZnO and ZnS can capture electrons and holes to extend their lifetime. The doping of ZnO by S can reduce its intrinsic bandgap to absorb visible light.